Diastolic dysfunction can precede systolic dysfunction on MUGA in cancer patients receiving trastuzumab-based therapy. Issue 1 (January 2019) - Klein, Ran; Nadouri, Doaa; Osler, Erin; Johnson, Christopher; Dent, Susan; Dwivedi, Girish
Abstract : Background: Trastuzumab (T) and anthracycline (A)-based chemotherapy is considered the standard of care in human epidermal growth factor receptor-2+ overexpressing breast cancer, but requires monitoring for known cardiotoxicity using left ventricular (LV) ejection fraction (EF) every 3–4 months during treatment. It is not conclusively established whether diastolic dysfunction (DD) precedes LVEF decrease in patients developing trastuzumab-induced cardiotoxicity (TIC). Objective: The aim was to elucidate whether DD precedes LVEF decrease in trastuzumab-treated patients being monitored with radionuclide multigated acquisition for TIC. Patients and methods: Patients treated with T±A-based chemotherapy who had undergone multigated acquisition were selected by date range (January 2006–September 2015). Up to four scans were analyzed per patient: (a) pre-A therapy, (b) pre-T therapy, (c) 4 months into T therapy, and (d) at end of T therapy. Baseline referred to the first scan of each patient (i.e. pre-A or pre-T). LV systolic and DD were defined as follows: EF less than 50% or a 10-point decrease from baseline and LV peak filling rate (PFR) less than 2.5 end-diastolic volume/s and time to peak LV filling rates (TPFR) greater than 180 ms, respectively. Results: A total of 202 patients were screened for this study, of whom 153 had received A therapy (5.1±4.1 months duration) before T, 192 had 4 months of follow-up data, and 146 had 4 months of follow-up data and beyond (10.5±5.0 months). LVEF decreased with A and T therapy ( P <0.005), but remained stable between 4 months and the final exam ( P =0.26). In patients with normal diastolic function at baseline (45.5%), PFR decreased with A and T, and DD preceded SD by 73 days on average. In the remaining patients, with abnormal diastolic function at baseline (54.5%), PFR did not change over the course of treatment ( P >0.1), nor did TPFR ( P >0.3). Conclusion: Patients with normal diastolic function at baseline receiving trastuzumab±anthracycline adjuvant therapy may develop DD before SD, therefore offering an opportunity for early referral to cardiologists to optimize cardiovascular risk factors and manage cardiotoxicity.